The Impact of Organizational Commitment, Flexibility, and Autonomy on Performance: JD-R-GROW Framework - Syaeful Bahri; Ahmad Zainuri; Yoga Adiyanto (PT ARRUS Intelektual Indonesia, 2026)
Purpose: This study investigates the influence of Organizational Commitment (X1), Workplace Flexibility (X2), and Work Autonomy (X3) on Employee Performance (Y), with Job Engagement (Z) acting as a moderating factor, within the context of the JD-R-GROW Framework at Dinas Kesehatan Provinsi Banten. Methodology/Approach: A quantitative research design was employed, with 141 respondents from Dinas Kesehatan Provinsi Banten. Structural equation modeling (SEM) using SmartPLS 3.0 was used to test the direct, moderating, and indirect effects of the variables. Results: All three independent variables (X1, X2, and X3) had significant positive effects on employee performance (Y). Job engagement (Z) significantly moderated and mediated the relationship between these organizational factors and employee performance. Conclusions: This study confirms that organizational commitment, workplace flexibility, and work autonomy positively influence employee performance, with job engagement playing a critical role in amplifying these effects. Limitations: The cross-sectional design and focus on a single healthcare organization limit generalizability. Future studies should employ longitudinal designs and include multiple organizations to enhance their external validity. Contributions: This study provides insights into how healthcare organizations can improve employee performance by fostering organizational commitment, offering workplace flexibility, and increasing work autonomy, while also focusing on enhancing job engagement.